Effect of Inoculant on the Degradation Behaviour of Multi Layered Mild Steel/Al-Cr Plate in Psidium Guajava Leaf Extract - Bawa, M. A.; Abdulwahab, M.; Umaru, O. B.; Adams, S. M.; Sani, L. M.; Agidani, N. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
The effect of an inoculant, [triethylamine (TEA)] on the corrosion behavior of multilayered mild steel/Al-Cr plates in guava leaf extract was investigated in 0.5M HCl solution using gravimetric based mass-loss test and potentiodynamic polarization techniques. The mild steel plates were sectioned into coupons of 4  and then pickled, after which they were coated at 750 with an Al-Cr alloy. The gravimetric-based mass loss test was carried out at room temperature for different concentrations and time intervals of 2.0, 4.0, 6.0, 8.0%v/v and 24, 48, 72, 96 hours respectively. The result showed that triethylamine (TEA) decreased the corrosion rate at the various concentrations indicating protection efficiency up to 59.02% in the gravimetric-based-mass-loss technique. Equally the potentiodynamic polarization technique indicates higher corrosion resistance of 98.49%. The two methods used for the evaluation of the degradation of multilayered mild steel/Al-Cr plates in 0.5M HCl/guava leaf extract medium were in agreement.